A brief history of Khubilai Khan - Clements, Jonathan (Robinson, 2010)
His grandfather was the bloodthirsty Mongol leader Genghis Khan, his mother a Christian princess. Groomed from childhood for a position of authority, Khubilai snatched the position of Great Khan, becoming the overlord of a Mongol federation that stretched from the Balkans to the Korean coastline. His armies conquered the Asian kingdom of Dali and brought down the last defenders of imperial China. Khubilai Khan presided over a glorious Asian renaissance, attracting emissaries from all across the continent, and opening his civil service to 'men with coloured eyes'. His story is contemporaneous with the legends of Prester John, the pinnacle of the samurai, and Marco Polo's extraordinary journey to Xanadu. It is also the story of one of the greatest dynasties in Chinese history.